Menu sehat untuk lanjut usia Dilengkapi dengan panduan menu beberapa penyakit / Emma S. Wirakusumah ; Penyunting : Erni Priyatini - Wirakusumah, Emma S.; Erni Priyatini (Puspa Swara, 2001)
vii,118 hlm. ; 23 cm.